Analisis Sistem Pelaporan Monitoring Efek Samping Obat (Meso) Oleh Tenaga Farmasi Di Puskesmas Kota Kendari - Wa Ode Sitti Nurrokhmadani; Adryan Fristiohady Lubis; Devi Savitri Effendy (Jurnal Sains & Kesehatan, 2025)
The extensive use of medicines in healthcare services carries the risk of adverse drug reactions (ADRs) that are not always detected during pre-marketing clinical trials. Therefore, a Monitoring of Adverse Drug Reactions (MESO) reporting system is required in healthcare facilities. This study aims to analyze the influence of knowledge, attitudes, barriers, and facilities on the implementation of MESO reporting by pharmacy personnel at primary health centers (Puskesmas) in Kendari City. The study employed an analytic quantitative cross-sectional design involving 68 pharmacy staff respondents and utilized bivariate chi-square and logistic regression analyses. The results showed that knowledge was not significantly associated with MESO reporting implementation (p=0.147), whereas attitude (p=0.027) and reporting barriers (p=0.004) demonstrated significant associations. Reporting facilities did not have a significant effect (p=0.188). Barriers such as workload and a complicated reporting system emerged as the main issues. In conclusion, optimizing MESO reporting requires strengthening positive attitudes, eliminating key barriers, and developing an integrated system to support sustainable reporting and improve the quality of healthcare services in primary health centers.